TRANSFER PRICING DECISIONS AT MULTINATIONAL COMPANIES IN INDONESIA: TAX EXPENSES, FOREIGN OWNERSHIP, INTANGIBLE ASSETS - Anggun Budi Utami S Depari; Reza Ramadhan; Amrie Firmansyah (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2020)
This study aims to examine the effect of tax expenses, foreign ownership on transfer pricing decisions. This study employs quantitative methods. This study's data type is secondary data from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. Data were obtained from the Indonesia Stock Exchange's official website at http: //www.idx.co.id. Sampling was conducted by purposive sampling technique with a final sample of 30 observations. Hypothesis testing is done by multiple regression analysis with panel data. This study concludes that tax expenses and intangible assets are positively associated with transfer pricing decisions, while foreign ownership is not associated with transfer pricing decisions. This study indicates that Indonesia's Tax Authority needs to exercise tighter supervision on MNCs with intangible assets.